Government size and economic growth in the Caribbean - Palmer, Ransford W. ([s.n.] [S.l.], 1994)
Examines the impact of government spending on economic growth in the Caribbean and the extent to which this impact is influenced by the relative size of government. Focuses on Jamaica, Trinidad and Tobago, Guyana and Barbados.